2006
DOI: 10.1002/biot.200600043
|View full text |Cite
|
Sign up to set email alerts
|

A rapid, high content,in vivomodel of glucocorticoid‐induced osteoporosis

Abstract: Glucocorticoid-induced osteoporosis (GIOP) is a major clinical problem given the widespread use of steroids and limited efficacy of biphosphonates. Existing animal models of GIOP are both slow and expensive. Hence, there is a need both for adjunctive modelling systems, as well as more efficacious therapies for the treatment of GIOP. We have addressed this issue through the creation of a zebrafish model of GIOP, which can be used for 96-well plate in vivo screening with an assay time of 5 days. The model demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
68
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(76 citation statements)
references
References 41 publications
7
68
0
1
Order By: Relevance
“…Excess GC also inhibits osteoblast differentiation and bone nodule formation in bone marrow stroma stem cells [1] , consistent with our previous studies [16] . Furthermore, previous reports indicate that GC induces the inhibition of osteogenesis in zebrafish larvae 21 , consistent with our present results.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Excess GC also inhibits osteoblast differentiation and bone nodule formation in bone marrow stroma stem cells [1] , consistent with our previous studies [16] . Furthermore, previous reports indicate that GC induces the inhibition of osteogenesis in zebrafish larvae 21 , consistent with our present results.…”
Section: Discussionsupporting
confidence: 94%
“…Since 2006, when Fleming et al [21] found that wild-type larval zebrafish exposed to prednisolone showed an obvious delay of skull mineralization based on alizarin red staining, zebrafish larvae have been widely used for the highthroughput screen for anti-osteoporotic candidates [22,23] . Tg (sp7:egfp) is a transgenic line zebrafish characterized by the osterix gene driven expression of green fluorescent protein (GFP) in osteoblast differentiation [24,25] .…”
Section: Original Articlementioning
confidence: 99%
“…The data revealed a marked bone loss in larvae treated with prednisolone. Furthermore, this prednisolone-induced bone loss was prevented by RU486, a glucocorticoid receptor (GR) antagonist (Barrett et al 2006). Our present study demonstrates that GIO also occurs in the adult European eel.…”
Section: Cortisol-induced Eel Vertebral Demineralizationsupporting
confidence: 52%
“…Recently, zebrafish larva was proposed as a rapid in vivo model of GIO (Barrett et al 2006) using staining mineralized tissue with fluorescent dye as a method to quantify bone size and density (Du et al 2001). The authors exposed zebrafish larvae in 96-well plates to different doses of GC pharmacological agonist (prednisolone) for 5 days.…”
Section: Cortisol-induced Eel Vertebral Demineralizationmentioning
confidence: 99%
“…However, with regard to bone density and quality, dogs appear to be most similar to humans and rats the least (Aerssens et al 1998). Interestingly, in vivo and in vitro bone mineral imaging as well as scale mineralization studies in zebrafish were described as a very simple alternative to explore alterations in mineralization pathways to GC challenge (Barrett et al 2006). …”
Section: Animal Species Used For Gc-induced Osteoporosis Modelsmentioning
confidence: 99%